Antibacterial compound from Euchema spinosum originated from Tasikmalaya West Java against pathogen bacteria with TLC-bioautography - Indra Topik Maulana; Rifa Safira; Inge Aprianti; Livia Syafnir; Reza Abdul Kodir (Pharmaciana, 2021)
Streptococcus mutans (Gram-positive) and Shigella dysenteriae (Gram-negative) are two types of pathogen bacteria. The use of synthetic antibiotics against both bacteria is known to impact the bacteria's resistance. E. spinosum from Tasikmalaya is a potential macroalgae as a source of an antibacterial compound for both bacteria. The research aims to determine the antibacterial metabolite compound from E. spinosum originated from Tasikmalaya against S. mutans and S. dysenteriae. The research was conducted through several stages, starting from phytochemical screening, gradual maceration using hexane, ethyl acetate, and methanol, determination of antibacterial activity, and TLC-bioautography. Phytochemical screening showed that both raw material and extracts contained alkaloids, flavonoids, and steroids. The result showed that hexane, ethyl acetate, and methanol extract could inhibit the growth of S. dysenteriae starting from a concentration of 400 µg/mL. However, only ethyl acetate extract can inhibit the growth of S. mutans, starting from a concentration of 20 µg/mL. The chromatogram of the hexane extract showed the presence of 6 spots, ethyl acetate extract showed 5, and the methanol extract showed only 4, resulted from the elution system, respectively. The TLC-bioautography against S. dysenteriae showed that there was the presence of three clear zones on the ethyl acetate extract, detected as flavonoid, and three clear zones on the methanol extract. The TLC-bioautography against S. mutans showed one clear zone on the chromatogram of ethyl acetate extract. According to the AlCl3 spray reagent confirmation test, the active compound was the flavonoid group.